Effects of supplementary strength program on generic and specific physical fitness in cadet judo athletes - Branco, B. H.; Marcondes, V. A.; de Paula Ramos, S.; Badilla, P. V.; Andreato, L. V. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to investigate the effects of a supplementary strength program on general and specific physical fitness in under-18 judo athletes. In total, 21 athletes were randomized into 2 groups: experimental group (EG: aged = 15.5 ± 1.2 years; body mass = 71.3 ± 10.6 kg; practice time = 5.1 ± 1.2 years) and control group (aged = 16.6 ± 0.5 years; body mass = 71.7 ± 11.0 kg; practice time = 5.6 ± 0.8 years). Athletes were submitted to anthropometry, generic physical fitness tests (countermovement jump, one-repetition maximum in bench-press, row, and half-squat machine), and specific field tests (isometric and dynamic judogi chin-up and Special Judo Fitness Test [SJFT]). All measurements were presented at baseline, and 8 athletes per group completed pre-training and post-training assessments. Both groups performed the same judo training routine, and the EG also performed 3/weekly/sessions of strength training for 8 weeks. All measurements were conducted during the competitive season. There were no differences in body mass, height, and body fat percentage after the training period (p > 0.05). Improvements were observed in maximal strength for bench press (26.6%), row (17.7%), half-squat machine (29%), dynamic judogi chin-up (33%), and the following SJFT responses: block A (16.7%), block B (11.3%), sum of 3 blocks (8.3%), heart rate after 1 minute (-7.0%), and index (-12.5%), representing performance improvement for the EG. It was concluded that 8 weeks of strength training was positive for general and specific performance. Finally, this strength program may help coaches to develop strength without changes in body mass.